Increased diagnosis of attention-deficit hyperactivity disorder despite stable hyperactive/inattentive behaviours: evidence from two birth cohorts of Australian children - Kazda, Luise; McGeechan, Kevin; Bell, Katy; Thomas, Rae; Barratt, Alexandra (My University, 2022)
Background Globally, ADHD diagnoses have increased substantially and there is concern that this trend does not necessarily reflect improved detection of cases but that overdiagnosis may be occurring. We directly compared ADHD diagnoses with ADHD-related behaviours and looked for changes across time among Australian children in a large, population-based prospective cohort study. Methods We conducted a secondary analysis of the Longitudinal Study of Australian Children, including 4,699 children born 1999/2000 (cohort 1) and 4,425 children born 2003/2004 (cohort 2), followed from 4 to 13 years of age. We compared pre-diagnosis parent-reported hyperactive/inattentive behaviour scores between newly diagnosed (incident cases) and undiagnosed children and fitted Cox's proportional hazards regression models to examine the relationship between birth cohorts 1 and 2 and the risk of incident ADHD diagnosis. Results Cumulative incident ADHD diagnoses increased from 4.6% in cohort 1 (born in 1999/2000) to 5.6% in cohort 2 (born in 2003/2004), while hyperactive/inattentive behaviour scores remained steady. Among ADHD diagnosed children, 26.5% (88/334) recorded pre-diagnosis behaviours in the normal range, 27.6% (n = 92) had borderline scores and 45.8% (n = 153) scored within the clinical range. Children born in 2003/2004 were more likely to be diagnosed with ADHD compared with those born in 1999/2000 (aHR = 1.33, 95% CI = 1.06–1.67, p = .012), regardless of their ADHD behaviour score (p = .972). Conclusions Diagnostic increases were not driven by rises in hyperactive/inattentive behaviours. A quarter of all children with an ADHD diagnosis recorded pre-diagnosis behaviours within the normal range. The increased likelihood of being diagnosed with ADHD for children from the later birth cohort was observed for children across the full range of ADHD-related behaviours.
Journal of Child Psychology and Psychiatry
Keywords: Adolescents and youth; Health and wellbeing